(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes foreign and national experiences in developing students’ reading competence. The study highlights the role of communicative, cognitive, and intercultural approaches in forming reading skills, emphasizing the interactive and reflective aspects of reading activities in modern education. A comparative analysis between the educational practices of the European Union, the United States, Japan, and Uzbekistan reveals effective strategies. The findings justify the need for using innovative technologies, individualized learning environments, and reflective methods to enhance students’ reading competence effectively